ANALISIS FAKTOR PENGGUNAAN FORMALIN PADA PEDAGANG TAHU DI PASAR TRADISIONAL KOTA SERANG - Fauzul Hayat; Darusmini Darusmini (Jurnal Surya Muda, 2021)
Formalin is known as a disinfectant, germicide and non-food preservative. For this reason, useing formalin in tofu food products is strictly prohibited. The importance of preventing the use of formalin in tofu traders has an impact on human health so it is safe for consumption. The purpose of this study was to determine of formaldehyde used among tofu traders in the traditional market of Serang City. Cross-sectional study with total sampling technique. The research sample was 43 tofu traders and 43 tofu samples were taken. Questionnaire instrument to obtain data on the variables of knowledge, attitudes and supervision variables that had previously been tested for validity (r count > r table) and reliability with Cronbach's alpha (α) value of 0.947 > 0.60. Tofu formalin content examination was carried out by the Regional Health Laboratory (Labkesda) Serang City using the Schiff reagent test. The results showed that there were (67.4%) tofu trader were positive formalin. There is no relationship between attitudes and use of formaldehyde in tofu traders (p=1,000). There is a relationship between knowledge (p=0.016) and supervision (p=0.004) with the use of formalin in tofu traders. Application of regulations, supervision traders and producers to prevent the use of formaldehyde in food.